The analysis of a resident on her didactic work with a double-entry table in physicochemistry classes evidences levels of pedagogical reflection - Scaine, Trinidad Rayen; Bachi, María Basilisa García; Cutrera, Guillermo (Revista Binacional Brasil-Argentina: Dialogue between the sciences, 2024)
The present research analyzed levels of pedagogical reflection evidenced in a resident’s analysis of her didactic work with a double-entry table in physicochemistry classes. Using a qualitative methodology, the text produced by the intern was examined, identifying contextualized modes of reflective writing. The results showed that the intern used different levels of reflection, moving from descriptions to didactic and critical dialogical reflections. Initially, she favored descriptive modalities to contextualize the table. She then moved on to higher-level reflections by deliberating on implications for learning, justifying didactic decisions, and proposing improvements. The transcription of discursive exchanges in the classroom allowed the resident to analyze her work by considering how the content circulated on the social plane. The inscription of writing modalities in the temporal sequence of the text expanded the analysis beyond the presence/absence of modalities and frequencies. Visualizing the succession of categories in the sentences made it possible to identify profiles that expressed different variations in reflexive levels.